The Ambivalence of Host and Discourse on Multiculturalism in Korean Reality TV Show - Fadhila Hasby; Lilawati Kurnia; Suma Riella Rusdiarti (CV. Media Digital Publikasi Indonesia, 2026)
South Korea implemented multiculturalism in 2006. The implementation of this policy became the backdrop for the emergence of multicultural television programs. Among the existing genres, reality TV shows were chosen by television stations to feature more immigrants on the screens of Korean viewers. Today, television programs have become an important space for representing immigrant identities to local audiences. This study analyzes a reality TV show titled My Neighbor Charles to gain a deeper understanding of the construction of immigrant representation in this program. This study assumes that the construction of immigrant representation is greatly influenced by how host Hong Seok Cheon frames the narrative of immigrant representation. Previous studies have not considered the important role of the host in framing the multiculturalism phenomenon in Korea. This study employs textual analysis and applies Critical Discourse Analysis to examine the data. Findings show that Hong simultaneously reinforces and criticizes the values and norms of the Korean majority. Rather than weakening Korea’s cultural dominance over immigrants, Hong’s ambivalent attitude strengthens its cultural hegemony.